WEBVTT
00:00:00.880 --> 00:00:08.240
Simplify 𝑏 to the power of four multiplied by 𝑎 to the power of four multiplied by 𝑏 to the power of two multiplied by 𝑎 to the power of five.
00:00:09.240 --> 00:00:19.920
Our first step is to group the like terms: 𝑎 to the power of four multiplied by 𝑎 to the power of five and the 𝑏 terms, 𝑏 to the power of four multiplied by 𝑏 to the power of two.
00:00:20.640 --> 00:00:24.200
We can then use one of the laws of exponents.
00:00:24.200 --> 00:00:29.560
𝑥 to the power of 𝑎 multiplied by 𝑥 to the power of 𝑏 is equal to 𝑥 to the power of 𝑎 plus 𝑏.
00:00:30.640 --> 00:00:43.440
Using this law on the 𝑎 terms, 𝑎 to the power of four multiplied by 𝑎 to the power of five means that we can add the two exponents or powers, giving us 𝑎 to the power of four plus five.
00:00:44.160 --> 00:00:52.280
In the same way, we can add the exponents or powers of the 𝑏 terms, 𝑏 to the power of four plus two.
00:00:53.200 --> 00:00:59.480
Four plus five is equal to nine, and four plus two is equal to six.
00:01:00.320 --> 00:01:06.040
Therefore, simplifying this expression gives us 𝑎 to the power of nine multiplied by 𝑏 to the power of six.
00:01:06.560 --> 00:01:14.840
As multiplication is commutative, this could also be written as 𝑏 to the power of six multiplied by 𝑎 to the power of nine.